Assessment of Convergent Processes in Exports and Imports of Transport Services between Ukraine and EU - Stasiuk, O.; Chmyrova, L.; Fediai, N. (Statistics of Ukraine, 2023)
The article discusses current issues in assessing the convergence processes in the external trade in transport services between Ukraine and EU in 2010–2022. The authors focus on the industry level and give their own definition of the term “convergence processes in the transport sector”. An assessment of the convergence processes in exports and imports of transport services between Ukraine and EU is conducted using two indices: Index of Revealed Comparative Advantage (RCA) and Grubel – Lloyd Index. These indices are defined as parameters of a comprehensive methodological approach assessing convergence processes in the transport sector between Ukraine and EU. RCA of the transport sector is used to determine the convergence of the levels of transport services between Ukraine and EU, allowing for the assessment of convergence processes using indicators of transport service exports by category of transport between Ukraine and EU. The reasons for the sharp decline in the exports of transport services between Ukraine and EU were identified. Grubel – Lloyd Index is used to assess convergence trends between Ukraine and EU by category of transport. It is demonstrated that intra-industry trade between EU and Ukraine by category of transport gives evidence of a significant increase in its level, characterizing the transport sector as high performing. Estimations based on RCA allowed to determine that rail and river transport had high comparative competitive advantages, which were lost by maritime transport. The estimated Grubel – Lloyd Index for the external trade in transport services between Ukraine and shows an upward tendency for most categories of transport in the analyzed period, except for maritime transport services. Further research on the topics discussed in the article will focus on assessing the sigma and beta convergence of the transport sector between Ukraine and EU.